Design and Evaluation Study of Performance of Optical Wireless Sensors Network for Achieving High Data Rate and Power Saving - Ibrahim, Isam Aameer; Mansour, Tahreer Safa's (International Journal of Interactive Mobile Technologies (iJIM), 2021)
Abstract—One of the major global issues today is the growing requirements for high-speed data transmission, energy consumption, and the huge volume of data utilized by a variety of multimedia applications such as video streaming, monitoring systems, and gaming. In this research, an analysis is carried out to study the design and evaluation of performance underwater OWC systems (UOWC) through medium communication link ranges to overcome absorption and scattering and to meet the requirements of a wide variety of optical wireless applications. Two modulation schemes of technology have been proposed in the UOWC system which is Differential Phase Shift Keying (DPSK) modulation with Direct Detection (DD) and the DPSK modulation with Coherent Detection (CD), both of them used Optical Orthogonal Frequency Division Multiplexing (OFDM) based on different configurations of multi-input multi-output technology (MIMO). The mathematical model has been proposed to calculate optimal beacon period (BI) and listen to the interval (LI) for preventing overlapping time between the signals and the required power is reduced. By using different types of water the simulation results are displayed the best performance of the UOWC system from link rang and receiver sensitivity. The simulation result of BER is equal 10-5, BI equal to 85ms, and LI equal to 108ms.